Estado nutricional y nivel socioeconómico de las madres de familia del club de madres "Jehová es mi Pastor”. Trujillo, febrero del 2013 - Quispe Pretel, Nathaly Lucia (2013)
We performed a cross-sectional descriptive study. The aim of this study was to establish the nutritional status and socioeconomic status of the mothers mothers club "The Lord is my Shepherd" liberators sector 7. The Miracle District Huanchaco - Trujillo March-April 2013. "The sample consisted of 34 mothers between 20 and 60, which were dividadas by age range 20-24 years, 25-40 years and 41-60 years. We used anthropometric measures (weight, height, waist / hip ratio, body mass index), classifying them in a state of malnutrition, normal, overweight or obese. The results with respect to BMI showed that mothers of 20-24 years comprendidades 66.70% overweight, while the mothers between 25-40 years and 41-60 years, 66, 70% and 40% are classified as preobesos respectively. Regarding the percentage of body fat, 33.3% of mothers between 20-24 years are classified as normal weight, between 25-40 years is 77.80% and the limit between 41-60 years mothers 56.3% are obese. As for the results of the waist / hip ratio of all the mothers were obese abdominovisceral 54.84% corresponding to mothers aged 20-24, 19.35% for those between 25-40 years and 25 85% between 41-60 years. To determine socioeconomic survey was applied to every mother, classifying lower class and lower-middle-class marginal. According to the results concluded that the mothers are mostly classified as nutritional state and a lower percentage preobesos state of obesity, lower socioeconomic class low-marginal